Sustaining Fixed Exchange Rates : A Model with Debt and Institutions - Pitt, Alexander (IMF Working Papers; Working Paper, 2001)
Fixed exchange rate regimes have come into disrepute, as their defense has become all but impossible. Yet, while a determined attack on a currency cannot be prevented or, ultimately, withstood, policies can reduce the vulnerability of a country to such attacks. The paper develops an analytical framework of costs and benefits of a fixed exchange rate, based on the ability of a developing country to meet its external obligations while achieving a maximum rate of long-term output growth. The focus is on how structural policies and institutions influence the degree of dependence of a country on a fixed exchange rate regime.